Dynamics of Multimodal Transportation and Freight Forwarding in Indonesia: A Comprehensive Analysis of Challenges, Strategic Roles, and Policy Responses - Anggraini, Liana Dwi; Tohir, Muhammad (Siber Journal of Transportation and Logistics, 2025)
Multimodal transport and freight forwarding play a crucial role in Indonesia's logistics system, especially given its archipelagic geography. This research analyzes the challenges, roles, and government initiatives related to these two sectors. Multimodal transport is defined as the carriage of goods using at least two different modes under a single contract, with the Multimodal Transport Operator (MTO) bearing full responsibility. Meanwhile, freight forwarding involves arranging and coordinating commodity shipments across borders, helping companies simplify processes and enhance efficiency. Notwithstanding their critical importance, Indonesia faces a number of obstacles in implementing multimodal transportation and freight forwarding, such as inadequate infrastructure, intricate regulations, operational problems, and a lack of human resource competency. The government has responded with initiatives such as the National Logistics System Masterplan (Sislognas), National Logistics Ecosystem (NLE) program, digitalization policies (IoT, AI), investment incentives, and human resource development programs. This study employs a comprehensive literature review approach, drawing from recent journals, articles, and books to qualitatively analyze the issues. The analysis reveals that synergy between multimodal transport and freight forwarding, supported by government policies and technology adoption, is essential for enhancing national logistics efficiency and global competitiveness. Recommendations include increased infrastructure investment, regulatory harmonization, accelerated digitalization, and strengthened human resource capacity and public-private partnerships.